Exploration of Religious Tourism in Sunan Giri Gresik as a Halal Tourism Destination (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
The development of world tourism now is Muslim-friendly tourism. The embodiment of religious tourism as Muslim-friendly religious tourism is a necessity. This research focuses on the exploration of Sunan Giri Gresik tourism services and facilities referring to nine indicators of Indonesian halal tourism and assessing the readiness of Gresik religious tourism as a halal tourism destination. The research method used is qualitative. Data collection techniques through field studies and documentation. Field studies were conducted through interviews and observations. Field studies were conducted through interviews and observations. The interview was conducted at the Head of the Gresik Regency Tourism and Culture Office, Chair of the Sunan Giri Mausoleum Foundation. Observations made include observing the availability of facilities and services around the Sunan Giri religious area referring to the nine indicators of halal tourism of the Indonesian Ministry of Tourism and Creative Economy. The results of the study show that Sunan Giri's religious tourism services and facilities meet the nine indicators of Indonesian halal tourism. Sunan Giri religious tourism is ready to be projected as a halal tourist destination based on the criteria of need to have, good to have, nice to have, namely the availability of the basic needs of Muslim-friendly tourists, able to provide a memorable experience for tourists, able to compete with other countries. In addition, it also has advantages in terms of facilities and infrastructure that are more complete, such as: souvenirs, management resources, service models, management standards, lodging and transportation availability.